2019
DOI: 10.1007/s10499-019-00365-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genetic analysis of natural and farmed populations of pike-perch (Sander lucioperca)

Abstract: Pikeperch (Sander lucioperca) is a native fish species in the European and Asian basin, representing high natural and economical value. However, our information on the genetic background and diversity of European populations is still limited, despite of that the production and the number of bread stocks has increased significantly in the last decade. Our aim was to develop new useable species-specific microsatellites and compare genetic diversity of ten pikeperch population from the Danube drainage basin. Thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…The mean number of alleles and the level of heterozygosity (He) were the second highest in the Hungarian farm population (Na = 7.55; He = 0.71) which exceeded the value of the wild population (Na = 6.00; He = 0.67). Kánainé Sipos et al (2019) estimated the genetic diversity of 10 pikeperch populations in the Danube basin (including Balaton and Attala populations) using a different microsatellite set. The genetic diversity of the two populations was moderate (Ar = 3.49 and 3.50 He = 0.46 and 0.52 in the Balaton and Attala population, respectively) compared to the other populations (Ar = 2.48-3.97 He = 0.48-0.59), but was lower than in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean number of alleles and the level of heterozygosity (He) were the second highest in the Hungarian farm population (Na = 7.55; He = 0.71) which exceeded the value of the wild population (Na = 6.00; He = 0.67). Kánainé Sipos et al (2019) estimated the genetic diversity of 10 pikeperch populations in the Danube basin (including Balaton and Attala populations) using a different microsatellite set. The genetic diversity of the two populations was moderate (Ar = 3.49 and 3.50 He = 0.46 and 0.52 in the Balaton and Attala population, respectively) compared to the other populations (Ar = 2.48-3.97 He = 0.48-0.59), but was lower than in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The basis of this variance is the genetic diversity of the native populations. The genetic diversity of the species was described in Aral-Lake (Khurshut & Kohlmann, 2009) and the Caspian Sea (Gharibkhani et al, 2009) and in Kazak (Barmintseva et al, 2014), French (Poulet et al, 2009;Louati et al, 2016), German (Eschbach et al, 2014), Fennoscandian (Björklund, Aho & Larsson, 2007;Säisä et al, 2010;Salminen et al, 2012), Russian (Kusishchin et al, 2018) and Hungarian (Kánainé Sipos et al, 2019) populations.…”
Section: Introductionmentioning
confidence: 99%
“…Wild populations analyzed in this study show moderate levels of genetic diversity for microsatellite loci (average Ar:3.8 and uH E :0.58) close to values previously referred for other wild populations of pikeperch in Europe. Kánainé Sipos et al [15], for example, reported values of Ar ranging 3.5-4.0 and H E ranging 0.46-0.59 in three natural water populations from the Danube catchment area. Säisä et al [11] compared three coastal and five freshwater populations of pikeperch in the northern part of the Baltic Sea drainage basin and reported average values of H E 0.34 (for coastal samples) and 0.42 (for the lake samples) and allelic richness of 3.6 (coastal) and 4.6 (lake samples).…”
Section: Genetic Diversity Of Wild and Domesticated Populationsmentioning
confidence: 99%
“…In the studied areas where the species has been introduced (i.e., south of France and west of Germany), populations display an unexpected high genetic diversity (i.e., similar to native areas; [3,7]), although it would have been lower due to founder effects and genetic bottleneck often happening during species introduction [14]. This is most likely a consequence of significant gene flow between allopatric populations through individuals' dispersion or human-made stocking [3,7] as observed in Northern European populations [8,15]. Despite these previous studies, the genetic structure and diversity of pikeperch populations over the species distribution range remain for the most part unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation